COMPARATIVE STUDY OF THE POST-OPERATIVE COMPLICATIONS OF CONVENTIONAL AND LAPAROSCOPIC INGUINAL HERNIA - SHAH, A. M.; AJAGEKAR, PRATIK D.; BHOSALE, SURESH J.; JEUR, AMOL; NAGVEKAR, MAYUR; NIKAM, YOGESH (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2021)
Hernia is probably the disease since mankind came into existence. The main reason for the intervention, however, remained the same, i.e. the continuous development of inguinal and scrotum inflammation, dislocation, strangulation risk, and the bad results of conservative methods such as truss placement. The study objective is to compare the post-operative complications of conventional and laparoscopic inguinal hernia repair with meshplasty. 100 patients were subjected to the inguinal hernia repair by prolene mesh by either conventional or laparoscopic techniques in Krishna Institute of Medical Sciences “Deemed To Be University” (KIMS), Karad during the period of from October 2015 to June 2017. The laparoscopic method requires, at least in unilateral situations, considerably longer operating times. The operation time is, however, not substantially different in bilateral situations. There is also a lengthy learning curve for the laparoscopic procedure and surgeons with more experience with the technique are capable of shorter operation times as well as less complications.